Integrated Coastal Zone Management in Ecological Planning - Etika Sukma Adiyanti (International Conference on Coastal and Delta Areas, 2015)
Functional relationships between ecosystems is a form of environmental harmony. The strategic location owned Indoneisa provide "PR penting" for planners with insight-led development planning. Coastal and delta have an important function in ecological planning. Because most of Indonesia is maritime zone. Marine nature itself has a functional purpose. For example, as a livelihood for fishermen, tourism opportunities, even the industry can take advantage of the presence of the sea.Development in Indonesian waters turned out to impair the function of the ecological integrity of the beach. It causes environmental degradation and decline in socio-economic welfare of the surrounding community. Similarly, river or sea border with the delta area will experience anxiety existence. Integrated coastal zone management can be a solution to these problems in the long term sustainable development. Its construction was substantially approach such an ecological approach, fungsioanlapproach, approach to social-political, and cultural approaches. While the instrumental approach including economic approach, the approach of the program, legal approaches, and alternative approaches. Step sequential process of development with that of the planning-implementationevaluation.